Enhancement of kenaf fiber mechanical properties through epoxy coating with nano silica particles: A comparative study of BE and BDE formulations - M.J. Meelad; Omar S. Dahham; N.Z. Noriman; Ahmad Z. Romli; M.F. Omar (Journal of Materials Research and Technology, 2025)
Natural fibres, such as kenaf, are biodegradable and sustainable materials valued for their abundance and ease of processing. However, their limited mechanical and thermal resistance restricts their broader application. This study investigates the enhancement of kenaf fibre properties through surface coating using epoxy resin filled with nano silica particles. The fibres were coated by dipping in a solution of epoxy and acetone (1:6 ratio) containing nano silica fillers. Two filler systems—BE and BDE—were prepared based on epoxy weight percentage and diluted epoxy weight percentage, respectively, with nano silica loadings of 1 %, 2 %, and 3 %. Results showed that coatings with 2 % and 3 % filler content exhibited improved stiffness and more efficient load transfer compared to 1 %. Overall, the presence of BE in the coating contributed to enhanced mechanical performance, including increased ductility, toughness, and resistance to deformation.